The Kinetic Features of the Palladium-Catalyzed Hydrogenolysis of Nitriles and Amines - Yap, Aaron J.; Masters, Anthony F.; Maschmeyer, Thomas (ChemCatChem, 2012)
A model of the kinetics underlying the hydrogenolysis of nitriles and amines, catalysed by Pd/C, has been derived. Benzonitrile and benzylamine were used as archetypical compounds to better understand the various reaction pathways involved in these processes. The reaction order under mild conditions (80 °C, 1 bar H2) for the hydrogenolysis of benzylamine was zero order in benzylamine, indicating strong adsorption of benzylamine to the catalyst, whereas the hydrogenation of benzonitrile was found to be first order in benzonitrile, owing to mass transport limitations, explaining the observed selectivities toward hydrogenolysis versus hydrogenation. Significantly, benzylamine itself was found to reversibly poison the hydrogenolysis function of the catalyst, preventing high yields of hydrogenolysis products at low catalyst loadings. An old friend revisited: A model of the kinetics underlying the hydrogenolysis of nitriles and amines, catalysed by Pd/C, has been derived. The kinetic features of these reactions were determined, enabling the investigation of the reasons behind the unusual preference for the continued hydrogenolysis observed under our mild conditions (80 °C, 1 atm H2).